Implementation of the Family Hope Program in Improving the Welfare of Poor Families - Tuwu, Darmin; Roslan, Suharty; Supiyah, Ratna; Sarpin (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to determine the implementation of the Family Hope Program in improving the welfare of poor families. This research is a qualitative research using a case study approach, where information data is collected through observation, interviews, and documentation. The results of this study show that the implementation of the Family Hope Program (FHP/CCT) in improving the welfare of poor families includes: first, the field of Education, which is a forum for improving human resources, namely through (CCT) to increase the access of the poor in education, as well as to reduce the number of children who drop out of school, and or difficulties in financing to continue education. Second, the health sector, which opens access for the poor to reach health services for infants, toddlers, and pregnant women, and the elderly and disabled. This paper contributes to the development of science related to the theme of social welfare programs